Effects of ursolic acid on growth performance, serum biochemistry, antioxidant capacity, and intestinal health of broilers - X.W. Zhang; X. Li; Y. Yin; M. Wang; Y.F. Wang; J.Y. Chen; Y.R. Zhao (Animal)
Previous studies have shown that adding 450 mg/kg of ursolic acid (UA) can improve the growth performance of broilers. However, the specific mechanism is still unclear. Therefore, the purpose of this study was to further explore whether UA promotes the growth of broilers by affecting the intestinal environment of broilers. We randomly divided 120 broilers with similar BW (46.53 ± 0.05 g) into two groups. Each group had six replicates, with 10 broilers per replicate. The broilers were fed either the corn-soybean meal−basal diet (CON group) or the corn-soybean meal−basal diet supplemented with 450 mg/kg UA (UA group). This study lasted 42 days. Adding UA increased the daily weight gain and feed conversion ratio of broilers (P < 0.05). The UA group exhibited reduced aspartate aminotransferase, total cholesterol, interleukin 6 and interleukin 1, and triacylglycerol levels, with increased interleukin 10 and high-density lipoprotein cholesterol in serum (P < 0.05). The UA supplementation improved total antioxidant capacity, total superoxide dismutase, and glutathione peroxidase activity in serum (P < 0.05), and increased these levels in the jejunum (P < 0.05). It reduced malondialdehyde concentration in the jejunum and ileum (P < 0.05), improved jejunal morphology by increasing villus height and villus-to-crypt ratio, and decreased crypt depth (P < 0.05). Gene expression of zona occludens 1 and Claudin-1 was higher, while interleukin 6 was lower in the UA group (P < 0.05). Additionally, interleukin 10 gene expression in jejunal mucosa was higher (P < 0.05). Significant differences were observed in the abundance of Bacteroides, proteobacteria, and desulfurisation bacteria (P < 0.05), with higher Barnesiella and Clostridia_UCG-014, and lower Romboutsia in the UA group (P < 0.05). Barnesiella negatively correlated with interleukin 6, interleukin 1, and triacylglycerol, but positively correlated with interleukin 10 (P < 0.05). In conclusion, adding 450 mg/kg UA to broiler feed can improve serum and jejunal antioxidant capacity, reduce jejunal and ileal inflammation, improve jejunal morphology, and regulate caecal microbiota structure composition, promoting broiler growth.